The Effect of Peppermint Aromatherapy on The Incidence of Emesis Gravidarum in The First and Second Trimester Pregnant Women in The Working Area of South Denpasar Public Health Center I, Denpasar City - I Gusti Ayu Ratih Agustini; Made Ririn Sri Wulandari; Kadek Putri Parasinta Dewi (Universitas Aisyah Pringsewu, 2022)
Emesis gravidarum is a condition that can cause weight loss, impaired body metabolism, malnutrition, weakness, and dehydration felt by the mother. Peppermint aromatherapy administered by inhalation can be a therapy that is able to overcome or eliminate nausea and vomiting in the first and second trimesters of pregnant women. The purpose of this study was to determine the effect before and after administering peppermint aromatherapy on the incidence of Emesis gravidarum in the first and second trimesters of pregnant women. This study was pre-experimental research with one group pretest-posttest design. The sampling technique used was accidental sampling consisting of 20 pregnant women in the first and second trimesters. Data was collected using observation sheets and PUQE-24 questionnaires. The results showed that the average value of nausea and vomiting before being administered peppermint aromatherapy was 8.15 (moderate category) and after being administered peppermint aromatherapy was 4.80 (mild category) with a difference of 3.35 and a significance value of 0.001 (p less than 0.05), statistically there was a significant difference in the mean of nausea and vomiting after being administered peppermint aromatherapy intervention. This study is expected to provide an overview of the importance of maintaining nutrition during pregnancy so that mothers are avoided chronic energy deficiency and prevent the long-term effects of emesis gravidarum. Mothers are expected to be able to independently implement the use of peppermint aromatherapy as an effort to reduce nausea and vomiting by using easily available ingredients. Abstrak: Emesis gravidarum merupakan keadaan yang dapat menyebabkan penurunan berat badan, gangguan metabolisme tubuh, kekurangan gizi, lemah, dan dehidrasi pada ibu. Aromaterapi peppermint yang diberikan secara inhalasi dapat menjadi salah satu terapi yang mampu mengatasi atau menghilangkan mual muntah pada ibu hamil trimester I dan II. Tujuan dari penelitian ini untuk mengetahui pengaruh sebelum dan setelah pemberian aromaterapi peppermint terhadap kejadian Emesis gravidarum pada ibu hamil trimester I dan II. Penelitian ini merupakan penelitian pre-eksperimental dengan desain One Group Pretest Posttest. Teknik pengambilan sampel yang digunakan yaitu dengan Accidental Sampling yang terdiri dari 20 ibu hamil trimester I dan II. Pengumpulan data dilakukan dengan menggunakan lembar observasi dan kuesioner PUQE-24. Hasil penelitan menunjukkan nilai rata-rata mual muntah sebelum diberikan aromaterapi peppermint sebesar 8,15 (kategori sedang) dan setelah diberikan aromaterapi peppermint sebesar 4,80 (kategori ringan) dengan selisih 3,35 dan nilai significancy 0,001 (p kurang dari 0,05) sehingga secara statistik terdapat perbedaan rerata mual muntah yang bermakna setelah diberikan intervensi aromaterapi peppermint. Penelitian ini diharapkan dapat memberikan gambaran terkait pentingnya menjaga nutrisi selama hamil agar ibu terhindari dari KEK serta mencegah efek jangka panjang dari emesis gravidarum. Ibu diharapkan dapat mengimplementasikan secara mandiri penggunaan aromaterapi pappermint sebagai salah satu upaya untuk mengurangi mual dan muntah dengan menggunakan bahan yang mudah didapatkan.